THE ROLE OF BRAND TRUST AS A MEDIATOR IN THE RELATIONSHIP BETWEEN SOCIAL MEDIA MARKETING AND PURCHASE INTENTIONS - Assyfa Meilyandra Panca Putri; Sularsih Anggarawati (Management Insight: Jurnal Ilmiah Manajemen, 2022)
Technological developments in Indonesia, especially in the internet sector, which continues to increase affect people's attitudes towards buying intentions, especially online. With a variety of information available online, it is easier for consumers to make purchases of a product. Instagram is one of the social media that can be used as a marketing and promotion medium by business people who can support online purchases. In online shopping, consumers consider aspects that need to be considered in generating purchase intentions. The purpose of this research is basically to find out how social media marketing affects purchase intention through brand trust. This research method is quantitative and the population in this study is Instagram Followers Scarlett Whitening, the number of samples obtained is 293 respondents. The sampling technique used is purposive sampling, with path analysis method. SmartPLS 3.29 For Windows is used to filter and analyze data. The findings reveal that social media marketing has a positive effect on purchase intention through brand trust. Practical advice in this study for Scarlett Whitening should increase brand trust. A company must continue to innovate to make products that are easily accepted by the market. And create interesting content marketing to create good social media marketing. It is expected to increase buying interest in Scarlett Whitening products. Keywords: Social Media Marketing, Purchase Intention, Brand Trust.